Logistic clusters: origins of formation and development prospects - Kuhan, Sviatlana F. (Journal of the Belarusian State University. Economics, 2021)
The history of the creation of clusters is closely intertwined with the history of the development of logistics. The interaction of business entities within the framework of cluster formations allows more efficient use of favorable market conditions in world markets. A study of scientific papers on this topic made it possible to present the genesis of cluster development as a combination of factors and formation conditions having unique characteristics at each historical stage. This made it possible to give a classification characterisation of the concept of «logistics cluster», to describe the conditions for its formation, participants and development directions (specialisation). The logistics cluster, as a network form of interaction between enterprises and organisations, enhances their competitive advantages and mitigates the negative effects of cross-country competition. The determination of the specialisation of the territory and the use of European experience in building cluster entities make it possible to integrate regional business entities in the framework of creating resource and process synergies of the logistics system.
Keywords: logistic system; cluster; network interaction; region; territory